The influence of self-efficacy and job satisfaction on teachers’ work engagement: empirical evidence from Junior High Schools in Bandung - Muhammad Syarif Hidayatullah; Rizki Amalia (ARKA INSTITUTE, 2026)
This study investigates how self-efficacy and job satisfaction shape work engagement among junior high school teachers in Bandung, Indonesia. A quantitative explanatory design was applied, collecting survey data from 401 teachers selected through stratified random sampling. Self-efficacy, job satisfaction, and engagement were measured with standardized scales and analyzed using Structural Equation Modeling (AMOS 26). Confirmatory factor analysis supported the adequacy of the measurement model, indicating acceptable convergent validity and composite reliability (AVE > 0.50; CR > 0.80). The structural model showed an acceptable fit (χ²/df = 2.14; CFI = 0.946; TLI = 0.938; RMSEA = 0.052). Hypothesis testing revealed that self-efficacy had a significant positive effect on work engagement (β = 0.41; p < 0.001), while job satisfaction exerted a stronger positive effect (β = 0.48; p < 0.001). Together, both predictors explained 61% of the variance in work engagement (R² = 0.61). In addition, job satisfaction partially mediated the association between self-efficacy and engagement (β = 0.19; p < 0.01), suggesting that confident teachers are more engaged partly because they feel more satisfied with their jobs. Overall, the findings highlight the value of strengthening personal and organizational resources to foster energetic, dedicated, and resilient teachers in demanding school contexts.